(untitled) (Al-Academy, 2025)
The study examined formal systems approaches to renovating the interior spaces of university libraries, with the aim of enhancing the role of libraries as living spaces for learning, social interaction, and knowledge transfer. The first section focuses on applying effective principles to develop the interior spaces of university libraries using environmentally friendly materials and integrating nature to enhance comfort and sustainability, including ecosystems and the effects of color on users. The researchers adopted a descriptive approach to analyze the selected model, concluding that technological progress drives the development of university library design, with a focus on exploiting natural resources and employing environmental and color elements to enhance the user experience. Recommendations included adopting systematic strategies to design flexible and sustainable interior spaces that take into account practical functions and aesthetic aspects as vital community centers.